Profitable Use of SCF in a Policy Context: the Case of Rice Stockholding in the Philippines - Christian D. Mina; Celia M. Reyes (Philippine Institute for Development Studies (PIDS), 2009)
This paper documents the activities of the National Food Authority (NFA), particularly on rice marketing, in realizing its mandates of buying high and selling low. Because the Philippine agriculture is greatly affected by extreme climate events such as El Ni\~no and La Ni\~na, this paper highlights the importance of seasonal climate forecast (SCF) information as input to the formulation of various policy decisions of the NFA. Among these important policy decisions are: how much volume of paddy rice to procure from farmers to be able to defend its support price; how much volume of rice to maintain in order to achieve stability in the supply and consumer price; and how much volume of rice, as well as when is the best time, to import to be able to position the optimal level of stocks in time for the lean season. It is also argued in the paper that importation has been playing a significant role in the rice supply-demand situation of the country since 1990, making it one of the most significant government interventions in the rice sector. Based on historical data assessment, some of the worst events in the past such as the 1995 rice crisis and over-importation during the 1997-1998 El Ni\~no could have been avoided if policy decisions, particularly on the volume and timing of rice importation, were linked to SCF. Indeed, linking crop production and import decisions more systematically with SCF would enhance the usefulness of these forecasts at a more practical level.
Keywords: 330; distribution; rice; seasonal climate forecast (SCF); National Food Authority (NFA); importation; storage; Reisanbau; Wetter; Agrarproduktion; Reis; Ernährungssicherung; Lebensmittelpreis; Philippinen